Cultivating mental wellness: a business plan for a holistic one-stop portal - Chen, Jiashu (2025)
This business plan outlines the development of "SoulGate," an innovative mental wellness one-stop portal. The platform aims to provide a centralised, accessible solution to address the global challenges associated with poor mental health. It leverages technology to offer users comprehensive mental health services, including online therapy, self-help resources, educational content, and community support.